Trans Hoogsteen/sugar edge base pairing in RNA. Structures, energies, and stabilities from quantum chemical calculations - Mládek, Arnost; Sharma, Purshotam; Mitra, Abhijit; Bhattacharyya, Dhananjay; Sponer, Jirí; Sponer, Judit E (The journal of physical chemistry. B, 2009)
Trans Hoogsteen/sugar edge (H/SE) RNA base pairs form one of the six families of RNA base pairs that utilize the 2'-hydroxyl group of ribose for base pairing and play key roles in stabilizing folded RNA molecules. Here, we provide a detailed quantum chemical characterization of intrinsic structures and interaction energies of this base pair family, along with the evaluation of solvent screening effects by a continuum solvent approach. We report DFT-optimized geometries and MP2 interaction energies for all 10 crystallographically identified members of the family, for a representative set of them, using complete basis set extrapolation. For 6 of the 10 base pairs, we had to apply geometric constraints to keep the geometries relevant to RNA. We confirm that the remaining, hitherto undetected, possible members of this family do not have appropriate steric features required to establish stable base pairing in the trans H/SE fashion. The interaction patterns in the trans H/SE family are highly diverse, with gas-phase interaction energies in the range from -1 to -17 kcal/mol. Except for the C/rC and G/rG trans H/SE base pairs, the interaction energy is roughly evenly distributed between the HF and correlation components. Thus, in the trans H/SE base pairs, the relative importance of electron correlation is noticeably smaller than in the cis WC/SE or cis and trans SE/SE base pairs, but still larger than in canonical base pairs. The trans H/SE A/rG base pair is the intrinsically most stable member of this family. This base pair is also known as the sheared AG base pair and belongs to the most prominent set of RNA base pairs utilized in molecular building blocks of functional RNAs. For all trans H/SE base pairs that we identified, in addition to conventional base pairing, viable alternative structures were stabilized by amino-acceptor interactions. In the QM calculations, these amino-acceptor complexes appear to be equally as stable as those with common H-bonds, and more importantly, the switch to amino-acceptor interaction does not require any significant geometrical rearrangement of the base pairs. Such interactions are worthy of further investigations, as X-ray crystallography cannot unambiguously distinguish between conventional and amino-acceptor interactions involving the 2'-hydroxyl group, formation of such interactions is usually not considered, and molecular modeling force fields do not include such interactions properly as a result of neglect of aminogroup pyramidalization.
Keywords: počítačová simulace; chemické modely; Quantum Theory; termodynamika; vodíková vazba; Thermodynamics; párování bází; kvantová teorie; RNA; Base Pairing; Computer Simulation; Models, Chemical; Carbohydrates; sacharidy; Hydrogen Bonding